COMMUNICATION AND CULTURE: SPEECH ACTS, SOCIAL ROLES OF POLITENESS AND LIES - Турсунова Парвина Мамуржоновна (Sciental Journals Publishing, 2025)
The article analyzes the relationship between communication and culture, the social functions of linguistic means, especially speech acts, the strategies of politeness and the social roles of lying on the basis of linguistic and socio-pragmatic approaches. The theory of speech acts explains the actions taken in the process of communication, intercultural differences in the norms of politeness, as well as the role of lies in mitigating conflicts and maintaining social balance. formation of modern communicative competence.
Keywords: Dialogue, culture, speech act, politeness, lies, pragmatics, language and society, communication